Review on the production of renewable biofuel: Solvent-free deoxygenation - Jeon, Kyung Won; Gong, Ji Hyeon; Kim, Min Ju; Shim, Jae Oh; Jang, Won Jun; Roh, Hyun Seog (Renewable and Sustainable Energy Reviews, 2024)
Biofuel is an eco-friendly fuel that can reduce CO2 emissions by 65% compared to using petroleum-based fuels. The commercialized biodiesel, which contains oxygen atom within its molecules, is only used in blends with petroleum-based diesel, but renewable diesel, diesel-like hydrocarbons, can completely substitute petroleum-based fuels. However, in the deoxygenation process to produce renewable diesel and jet fuel, solvents are injected to enhance the physical properties of reactants and the supply of hydrogen, thereby increasing the process expenditure. Therefore, in this review, the research results published over the past 10 years regarding the production of renewable fuels under solvent-free conditions have been critically reviewed. The effects of feedstocks, atmospheric conditions (type of gas and pressure), reaction temperature/time, catalyst type and its loading on the reaction mechanism and catalytic performance are carefully compared. Fatty acids and triglycerides require deoxygenation reactions, while furan compounds necessitate not only deoxygenation but also aldol condensation reactions to produce renewable biofuel. Higher H2 pressure and reaction temperature can enhance the reaction activity, but these parameters should be optimized while considering the process cost and side reactions. Noble metal catalysts have been reported to exhibit high deoxygenation activity, but for economic reasons, non-noble transition metals are being widely investigated. Ni is the most commonly used catalysts, and the deoxygenation mechanism varies depending on the acidity and type of acid sites on the catalyst. The feasibility of biofuels produced by solvent-free deoxygenation is assessed by comparing fuel properties with commercial diesel and jet fuel.
Keywords: CO 2 emission; Deoxygenations; Eco-friendly; Oxygen atom; Reaction conditions; Reaction temperature; Renewable biofuel; Renewable diesels; Solvent free; ]+ catalyst; Catalyst; Deoxygenation; Reaction condition; Renewable biofuel; Solvent-free